The Impact of Standardized Salaries on Teachers Motivation and Job Satisfaction: Implications for Education Policy Makers in Cameroon - Genevarius Nji (Program Pascasarjana Universitas Muhammadiyah Palu, 2026)
The main purpose of this study was to examine the impact of standardized salaries on teachers’ motivation and job satisfaction with implications for school administrators in Cameroon. The mixed method design was adopted for the study whereby by both quantitative and qualitative designs were employed. As instruments, Questionnaire and interview guides were used. Using the simple random and snowball sampling techniques, a sample of 254 teachers were selected from 6 schools. 15 secondary school teachers were selected for the study. Quantitative data was analysed using means and standard deviations while qualitative data was analyzed using thematic analysis. The findings prove that standardized salary system in Cameroon's education in spite it advantages in the education sector has created perceptions of unfairness and de-motivation among teachers which has led to lack of teacher commitment in curriculum implementation to a greater extend. Teachers who perceive their salary as being fair are motivated to work harder and vice versa. Based on the findings, recommendations were made to education stakeholders.